Religious Leadership and Personal Branding of 'Kyai' in Islamic Education Management: Pathways to Promoting Moderation and Preventing Radicalism - Misdah; Soemantri , Asep Iwa; Sumin, Sumin; Wajdi, Muh Barid Nizarudin; Pamungkas , Muhamad Imam (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Religious leaders are crucial in fostering moderate attitudes and behaviours, particularly among students of Pesantren (Islamic boarding schools). However, empirical studies examining the relationship between Kyai leadership and efforts to counter radicalism still need to be explored. This study investigates the impact of religious leadership and personal branding of the Kyai on religious moderation and the prevention of radicalism in Pesantren. A quantitative approach with a correlational survey design was employed, involving 340 respondents, including administrators, students, and alums from Pesantren. Data were collected via a five-point Likert scale questionnaire administered online and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that religious leadership and personal branding of the Kyai positively influence religious moderation, which plays a vital role in countering radicalism. Additionally, religious moderation was found to mediate the relationship between Kyai leadership and personal branding with radicalism prevention. The restricted sample coverage due to the online survey format is a study limitation. The findings suggest that enhancing Kyai's religious leadership and personal branding can be a valuable strategy for combating Pesantren's radicalism.